2005
DOI: 10.1002/pds.1162
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, incidence and persistence of antipsychotic drug prescribing in the Italian general population: retrospective database analysis, 1999–2002

Abstract: An epidemiologically relevant proportion of everyday individuals is annually exposed to antipsychotic drugs. The distribution of prevalence and incidence rates by age highlighted an emerging public health issue related to the adverse and beneficial consequences of antipsychotic drug exposure in the elderly. The finding that persistence with therapy was longer in new users of novel antipsychotic drugs compared with new users of conventional agents might be explained by the different demographic and clinical cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 46 publications
3
31
0
Order By: Relevance
“…A dramatic increase in the use of atypical agents in the general population, and particularly in elderly demented outpatients, starting from their marketing until 2002, was previously reported in Italy (Trifirò et al, 2005;Mirandola et al, 2006), as well as in UK and US (Ashcroft et al, 2002;Hermann et al, 2002). In Italy, thereafter, national statistics have shown that the increase in the use of atypicals slowed down after 2004, which is consistent with our findings and compatible with an effect of safety warnings.…”
Section: Discussionsupporting
confidence: 94%
“…A dramatic increase in the use of atypical agents in the general population, and particularly in elderly demented outpatients, starting from their marketing until 2002, was previously reported in Italy (Trifirò et al, 2005;Mirandola et al, 2006), as well as in UK and US (Ashcroft et al, 2002;Hermann et al, 2002). In Italy, thereafter, national statistics have shown that the increase in the use of atypicals slowed down after 2004, which is consistent with our findings and compatible with an effect of safety warnings.…”
Section: Discussionsupporting
confidence: 94%
“…Such results were obtained in the ESEMeD project [11] and in more recent studies in Italy [20], Germany [21], France [22] and Switzerland [19]. In Swiss adult population, it was found that women have received benzodiazepine prescriptions in 67% cases, and half of all patients were at age 65 or older.…”
Section: Discussionsupporting
confidence: 66%
“…These studies were from Italy, [4][5][6] the United Kingdom, 7 and the United States. 8 The US study was found to be a case series concerned with phenothiazine and butyrophenone poisonings.…”
Section: Methodsmentioning
confidence: 99%
“…4 ; however, in the population studied, typical antipsychotics were used more frequently than atypical antipsychotics in each of the 4 years. This provided a stark contrast with the situation in some other countries, as described below.…”
Section: European Estimatesmentioning
confidence: 99%